2005
DOI: 10.1124/jpet.104.082784
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Endothelial and Smooth Muscle Phosphatidylinositol 3-Kinase in Vasoconstriction: Effects of Rho-Kinase and Hypertension

Abstract: Phosphatidylinositol 3-kinase (PI3K) can activate endothelial nitric oxide synthase (eNOS), leading to production of the vasodilator NO. In contrast, vascular smooth muscle (VSM) PI3K may partially mediate vascular contraction, particularly during hypertension. We tested whether endothelial and VSM PI3K may have opposing functional roles in regulating vascular contraction. Secondly, we tested whether the procontractile protein rho-kinase can suppress endothelial PI3K/eNOS activity in intact arteries, thus cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
25
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
8
25
1
1
Order By: Relevance
“…We recently reported that in aorta, where the predominant endothelium-derived relaxing factor is NO, effectiveness of rho-kinase inhibition is much greater in the presence of endothelium and, more specifically, endothelial NO synthase activity (Budzyn et al, 2005). This observation is consistent with the concept that there are several levels of interaction between rho-kinase and endothelial NO (Takemoto et al, 2002;Budzyn et al, 2004;Wolfrum et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…We recently reported that in aorta, where the predominant endothelium-derived relaxing factor is NO, effectiveness of rho-kinase inhibition is much greater in the presence of endothelium and, more specifically, endothelial NO synthase activity (Budzyn et al, 2005). This observation is consistent with the concept that there are several levels of interaction between rho-kinase and endothelial NO (Takemoto et al, 2002;Budzyn et al, 2004;Wolfrum et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Hodges and colleagues (19) found that full expression of cold-induced VC involves a decrease in eNOS activity and/or nitric oxide production but did not speculate as to the mechanism(s) through which localized skin cooling might regulate the eNOS pathway. Just as nitric oxide (through cyclic GMPdependent protein kinase) counters Rho kinase-mediated VC by activating myosin light chain phosphatase (7) and inhibiting activation of upstream RhoA (35), RhoA and Rho kinase similarly downregulates several steps in the eNOS pathway: decreased eNOS gene expression (30), decreased eNOS mRNA expression (13), eNOS mRNA destabilization (26,41), decreased eNOS protein expression (6,13,41), decreased activation of eNOS (6,8,30), and increased arginase activity, which decreases nitric oxide bioavailability (5,29). With a consideration for the interaction of these two systems under other conditions and in other vascular beds, it is plausible that they may interact in the cutaneous circulation during cooling, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Most attention has focused on the pathways involved in cell growth and migration; however, within the last few years, PI3-K activity has been implicated in vascular smooth muscle contractility and relaxation (3,22,26,31,32). Several groups have presented evidence that links PI3-K activity and phosphatidylinositol 1,4,5-trisphosphate (PIP 3 ) production to the opening of voltage-gated and receptor-coupled Ca 2ϩ channels (25,26,38).…”
mentioning
confidence: 99%